2018
DOI: 10.1093/hmg/ddy436
|View full text |Cite
|
Sign up to set email alerts
|

Kctd13-deficient mice display short-term memory impairment and sex-dependent genetic interactions

Abstract: The 16p11.2 BP4-BP5 deletion and duplication syndromes are associated with a complex spectrum of neurodevelopmental phenotypes that includes developmental delay and autism spectrum disorder, with a reciprocal effect on head circumference, brain structure and body mass index. Mouse models of the 16p11.2 copy number variant have recapitulated some of the patient phenotypes, while studies in f lies and zebrafish have uncovered several candidate contributory genes within the region, as well as complex genetic inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 85 publications
(100 reference statements)
13
39
0
Order By: Relevance
“…However, recent studies reported no robust abnormalities in brain structure of mice with genetic ablation of Kctd13, and instead observed sex-specific differences in brain volume of double heterozygous mice lacking one copy of Kctd13 and one copy of either Lat or Mvp, also located in 16p11.2. 75 These results suggest that altered dosage of Kctd13, and Mvp or Lat may have epistatic effects on brain size.…”
Section: Kctd13 Association With Autism and Schizophreniamentioning
confidence: 86%
See 2 more Smart Citations
“…However, recent studies reported no robust abnormalities in brain structure of mice with genetic ablation of Kctd13, and instead observed sex-specific differences in brain volume of double heterozygous mice lacking one copy of Kctd13 and one copy of either Lat or Mvp, also located in 16p11.2. 75 These results suggest that altered dosage of Kctd13, and Mvp or Lat may have epistatic effects on brain size.…”
Section: Kctd13 Association With Autism and Schizophreniamentioning
confidence: 86%
“…Other studies demonstrate that in mouse models, Kctd13 epistatically affects anatomical phenotypes in combination with Mvp (major vault protein) or Lat (linker for activation of T cells) , genes, which are also located in 16p11.2 loci. However, recent studies reported no robust abnormalities in brain structure of mice with genetic ablation of Kctd13 , and instead observed sex‐specific differences in brain volume of double heterozygous mice lacking one copy of Kctd13 and one copy of either Lat or Mvp , also located in 16p11.2 . These results suggest that altered dosage of Kctd13 , and Mvp or Lat may have epistatic effects on brain size.…”
Section: Kctd Genes Associated With Neurodevelopmental and Neuropsychmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass-univariate statistical analysis of whole-brain volume maps was performed in 146 postpubertal individuals as described [34]. Mouse MRI was performed as detailed in [35].…”
Section: Brain Structural Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…Interestingly, a significant number of ASD genes have been shown to play important roles in gene expression regulation, including transcriptional factors, chromatin remodeling factors and other types of epigenetic regulators, such as CHD8, FMR1, MECP2, and so on [Alonso-Gonzalez, Rodriguez-Fontenla, & Carracedo, 2018;De Rubeis et al, 2014]. Accordingly, numerous loss of function animal models were generated, especially the mouse models, to recapitulate the disease phenotypes and to explore the underlying molecular mechanisms [Araujo et al, 2017;Arbogast et al, 2018;Caubit et al, 2016;Celen et al, 2017;Cheng et al, 2018;Gabel et al, 2015;Harrington et al, 2016;Huang et al, 2018;Jung et al, 2018;Kong et al, 2014;McGill et al, 2018;Prilutsky et al, 2015;Provenzano et al, 2016;Raman et al, 2018;Scandaglia et al, 2017;Sgado et al, 2013;Suetterlin et al, 2018;Zhao, Goffin, Johnson, & Zhou, 2013]. With these models, RNA-Seq or microarray experiments have been performed in various brain regions to identify the downstream targets of the corresponding ASD genes.…”
Section: Introductionmentioning
confidence: 99%